THU0169 One-third of patients with rheumatoid arthritis eligible for a first biologic are not adherent to methotrexate: results of forget, a cross-sectional survey of 244 patients. (15th June 2017) - Beauvais, C; Hautin-Monteil, V; Ducrot, M-C; Flipo, R-M
Abstract : Background: Adherence to Methotrexate (MTX) is not optimal in patients with rheumatoid arthritis (RA)[1]. Low adherence may lead to insufficient response and unjustified initiation of biologics. Objectives: The objectives were 1-assess the self-reported adherence rate to MTX of RA patients insufficient responders to MTX (MTX-IR) when an initiation of biologics was being considered 2- Investigate the factors of low adherence among these patients 3- collect the physicians' estimation of their patients' adherence level. Methods: Patient recruitment was done through rheumatologists: RA patients, MTX-IR, biologic-naive, eligible for a biologic according to the rheumatologist's opinion. The rheumatologist completed a questionnaire on his practice and estimation on the patient's level of adherence and provided the patient with a self-administered questionnaire on his disease and treatments, to be sent directly to the data center. The patient's questionnaire contained the CQR19 (Compliance Questionnaire for Rheumatology [2]. The purpose of assessing adherence was not specified to the patient. Results: From May to July 2016, 78 rheumatologists recruited 269 patients who referred 244 self-administered questionnaires, 214 assessed for CQR 19 score; 200 questionnaires were completed by both patients and their rheumatologist. Patients were 72% women, mean age 54 years, 58% had at least 1 comorbidity, mean DAS28 score 4.07, mean RAID score 5.7/10. The percentage of non-adherent patients was 34%: adherence rate <80% according to the CQR. Non-adherent patients had a higher RAID score (5.7 vs 5.0; p<0.01) whereas DAS 28 was not significantly different (4.14 vs 4.04). They more often presented osteoporosis (18% vs 4%, p<0.01), reported reluctance to take treatment (40% vs 24%, p<0.01), had more negative beliefs (40% vs 24%; p<0.01), and poor support from relatives (67% vs 84%, p<0.011). Good-adherent patients were more often followed in a private practice (31% vs 10%, p<0.01) and reported more information received from their rheumatologist (94% vs 85%, p<0.05). No correlation was found between adherence and age, subcutaneous versus oral route of administration or perceived tolerance. 88% of rheumatologists reported they detect adherence at every consultation, asking direct (76%) or open (46%) questions. Adherence was underestimated by rheumatologists: a 67% concordance was found between the rheumatologist's rating and the patient's reported adherence. Non-adherent patients to MTX were more often proposed biologic treatment in combination with MTX than patients with good compliance (91% vs 68%, p<0.01). Conclusions: This survey showed for the first time that 34% of MTX-IR patients show poor adherence to MTX at the time of the initiation of a first biologic. Negative beliefs and poor support from relatives are factors of non-adherence. Studies will be needed to understand physicians' attitudes toward non-adherence and what strategy of biologics prescription they are likely to consider. References: DiBenedetti D Rheumatol Ther 2015. de Klerk E et al, J Rheumatol 1999. Acknowledgements: This study was funded by Chugai Pharma France. Disclosure of Interest: C. Beauvais: None declared, V. Hautin-Monteil Employee of: Roche France, M.-C. Ducrot: None declared, R.-M. Flipo: None declared